Triterpenoids from the Schisandraceae family: an update. Issue 3 (8th December 2014) - Shi, Yi-Ming; Xiao, Wei-Lie; Pu, Jian-Xin; Sun, Han-Dong
Abstract : Plants from the Schisandraceae family produce architecturally interesting triterpenoids, including lanostanes, cycloartanes, and schinortriterpenoids. This review focuses on their structures, classifications, biogenetic pathways, syntheses, and bioactivities (from February 2008 to May 2014). Abstract : Covering: February 2008 to May 2014. Previous review: Nat . Prod . Rep ., 2008, 25, 871–891 Several significant advances in the field of phytochemistry were made between 2008 and 2014 because of the high level of interest in Schisandraceae triterpenoids. In addition to a dramatic increase in the number of newly identified triterpenoids, the first complete synthesis of a schinortriterpenoid was accomplished. There has also been substantial progress in investigations of biological activity and mechanism of action. In this update, we review more than 250 new triterpenoids and describe their structures, classifications, biogenetic pathways, syntheses, and bioactivities.